Consistency between self-reported alcohol consumption and biological markers among patients with alcohol use disorder – A systematic review. (May 2021) - Grüner Nielsen, Dorthe; Andersen, Kjeld; Søgaard Nielsen, Anette; Juhl, Carsten; Mellentin, Angelina
Highlights: Self-reported alcohol consumption should be supplemented by biomarkers. Assessment on self-reported alcohol intake should cover a relevant time span. Biomarkers should be direct markers of alcohol. Biomarkers should cover a relevant time span. Inconsistency between self-reported alcohol consumption and biomarkers may occur. Abstract: Background: No systematic review has yet examined the consistency between self-reports of alcohol consumption and alcohol biomarkers among patients in treatment for alcohol use disorders (AUD). Therefore, we aimed to provide an overview of the consistency between self-reported alcohol intake and biomarkers among patients in treatment for AUD. Methods: The electronical databases MEDLINE, PsycINFO, EMBASE, Cochrane Database of Systematic Reviews (CDSR) and CENTRAL were searched for all original studies that examined the validity of self-reported alcohol consumption using a biological marker in samples of patients with AUD. Eligible studies were included in a qualitative synthesis of the outcomes. Quality assessment was conducted with the quality assessment tool for Observational Cohort and Cross-sectional studies, developed by The National Heart, Lung and Blood Institute. Results: The search identified 7672 hits, and 11 papers comprising 13 eligible studies were included. All the identified studies revealed inconsistencies between self-reporting and biomarkers. Under-reporting was the most common type of inconsistency across short-, intermediate- and long-term biomarkers. For short-term markers, under-reporting was indicated in 7 studies (n = 15–585) in a range from 5.5%–56.0% of the patients, and over-reporting in 2 studies (n = 34–65) in a range from 5.9%–74.1%. Only under-reporting was reported for intermediate-term, direct markers and was indicated in 2 studies (n = 18–54) in a range from 5.0%–50.0% of the patients. Although the results for long-term biomarkers were not reported consistently across the studies, under-reporting was indicated in 3 studies (n = 73–1580) in a range from 0.1%–40.0% of the patients, and over-reporting in 2 studies (n = 15–1580) in a range from 13.0%–70.6%. Correlations between self-reported alcohol consumption and biological markers were strongest for the intermediate-term direct markers, ranging from moderate to strong. For short-term and long-term markers, the correlations were mostly weak. Most of the studies were quality rated as fair. Conclusion: The findings indicate that inconsistency between self-reported alcohol consumption and biomarkers may occur in a considerable proportion of patients with AUD. However, further studies applying more sensitive, specific, and easily assessable biological markers are warranted to confirm this preliminary synthesis. PROSPERO registration no.: CRD42018105308